ADVANCING ANATOMICAL EDUCATION: THE ROLE OF 3D VIDEO-BASED LEARNING (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Anatomical education is a core component of medical training, yet traditional methods like lectures and cadaver dissections often fail to provide the depth of spatial understanding required for clinical practice. With the advent of educational technology, 3D video-based learning has emerged as a promising tool that may improve anatomical education. This study compares the effectiveness of 3D video-based learning apart from traditional teaching methods in enhancing students' understanding of human anatomy. Methodology: A total of 100 MBBS first-year students participated in the study. These students were divided into two groups based on the parity of their roll numbers: Group A (Traditional Teaching) includes even roll numbers and Group B (3D Video-Based Learning) includes odd roll numbers. Group A followed the conventional anatomy curriculum, which included lectures, textbook study, and cadaver dissection. Group B was introduced to 3D video-based learning tools apart from their regular curriculum, which provided interactive, immersive visualizations of anatomical structures, enabling students to explore and manipulate 3D structure of the skull. Both groups completed a MCQ exam after the learning module. The quiz was designed to test; Basic anatomical knowledge (e.g., identification of structures), Comprehension of anatomical relationships and Spatial understanding of how structures interact within the skull. The exam consisted of 30 multiple-choice questions, each targeting specific learning outcomes. Group A took the exam based on the traditional learning methods, while Group B took the same exam after engaging with 3D video-based content. Both groups were given the same amount of time to complete the exam. The performance of both groups was analysed to evaluate differences in examination scores. Result: Group a (Traditional Teaching): The average score for Group A was 68%. Students excelled in factual recall questions but performed poorly on questions that required spatial visualization of anatomical structures. Group B (3D Video-Based Learning): Group B scored significantly higher, with an average score of 82%. They performed better on questions requiring spatial understanding and the relationship between anatomical structures. Statistical analysis a significant difference indicating that 3D video-based learning was more effective. Conclusion: This study demonstrates that 3D video-based learning significantly improves students' understanding of human anatomy, particularly in spatial visualization. The findings suggest that 3D technologies can complement traditional teaching methods, enhancing the learning experience for medical students. Further research is needed to assess the long-term effects and scalability of these tools in medical education.